Hubungan Bauran Pemasaran dengan Peningkatan Pemanfaatan Rawat Inap (Studi di Rumah Sakit X Kelas C Kota Surabaya) - Ramadhani, Dina Dwi; Wijaya, Hermanto; Putri, Linta Meyla; Tjokro, Silvia Haniwijaya (Bagian Penelitian & Pengabdian Masyarakat STIKES Adi Husada, 2023)
Background: Marketing is a management activities derived from customer interactions. The marketing mix is one of the marketing techniques used by an organization to achieve its goals in the target market. The conditions required or that may be identified in order to use the available bed. In usage, four criteria are used for correctly tracking the usage of bed: bed occupancy ratio (BOR), length of stay (LOS), turn over interval (TOI), and bed turn over (BTO). According to information from Hospital X type C, the number of Bed Occupancy Rate (BOR) inpatients is below standard and will continue to fall throughout each month in 2022. Aims:The objective of this research was to investigate the association between the marketing mix and increasing utilization of inpatient care. Methods:This research conducted a quantitative study using a cross-sectional study technique. The sample was 20 persons. Results:Using all of the data generated by the independent variables and the dependent variable, namely the marketing mix and purchasing decisions, it is possible to determine product, price, place and process with a significance level smaller than 0.05, indicating that there is a relationship between these variables and the purchase decision. Conclusion: The utilization of inpatient rooms at Hospital X is influenced by several factors such as the service products offered, rates, place and process